« Les enfants veulent jouer au football, pas être exploités! » Coupe du monde de football 2014 et implications sur le tourisme sexuel infantile dans la ville d'accueil de Recife, Brésil. Issue 2 (4th May 2019) - Castilho, César Teixeira; Evrard, Barbara; Charrier, Dominique
Abstract : This study aims to analyze the issue of child sex tourism and its correlations with sports mega-events taking into consideration the implementation of preventive public policy in the host city of Recife – located in Northeast Brazil – in the context of the FIFA Football World Cup in 2014. Through a qualitative approach – interviews, observations, and photographs – this theme will be analyzed while taking into account the social aspects and the implications of excluded sectors of society in the organization of so-called mega-events. Although in the short term, the results obtained in the analyzed projects have been satisfactory, in the long run, effective social and educational measures must be prioritized to improve the situation of the actors involved. The topic of child sex tourism remains marginal in the context of sports mega-events, particularly in countries where social inequality persists.